Associations between P3a and P3b amplitudes and cognition in antipsychotic-naïve first-episode schizophrenia patients. Issue 5 (19th June 2018) - Kruiper, Caitlyn; Fagerlund, Birgitte; Nielsen, Mette Ø.; Düring, Signe; Jensen, Maria H.; Ebdrup, Bjørn H.; Glenthøj, Birte Y.; Oranje, Bob
Abstract: Background: Cognitive deficits are already present in early stages of schizophrenia. P3a and P3b event-related potentials (ERPs) are believed to underlie the processes of attention and working memory (WM), yet limited research has been performed on the associations between these parameters. Therefore, we explored possible associations between P3a/b amplitudes and cognition in a large cohort of antipsychotic-naïve, first-episode schizophrenia (AN-FES) patients and healthy controls (HC). Methods: Seventy-three AN-FES patients and 93 age- and gender-matched HC were assessed for their P3a/b amplitude with an auditory oddball paradigm. In addition, subjects performed several subtests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Results: AN-FES patients had significantly reduced P3a/b amplitudes, as well as significantly lower scores on all cognitive tests compared with HC. Total group correlations revealed positive associations between P3b amplitude and WM and sustained attention and negative associations with all reaction time measures. These associations appeared mainly driven by AN-FES patients, where we found a similar pattern. No significant associations were found between P3b amplitude and cognitive measures in our HC. P3a amplitude did not correlate significantly with any cognitive measures in either group, nor when combined. Conclusions: Our results provide further evidence for P3a/b amplitude deficits and cognitive deficits in AN-FES patients, which are neither due to antipsychotics nor to disease progress. Furthermore, our data showed significant, yet weak associations between P3b and cognition. Therefore, our data do not supply evidence for deficient P3a/b amplitudes as direct underlying factors for cognitive deficits in schizophrenia.